(untitled) (Bangladesh Journal of Medical Science, 2024)
Background It has been reported that using mouthwashes can discolour the surface of teeth. Their effect on the stainability of newly introduced lithium disilicate ceramics is, however, unknown. Objective: The purpose of this in vitro study was to investigate how mouth washes affected the color change of new and conventional lithium disilicate (LS2) ceramics that were finished using various techniques. Materials and Methods A total of 56 ceramic slices were produced from conventional LS2 (E Max CAD, Ivoclar) and a novel virgilite based LS2 (Cerec Tessera, Dentsply Sirona). According to the finishing method, the specimens were divided into glazed and polished subgroups. Each subgroup was further subdivided into two based on immersion in chlorhexidine (CHXD) or Listerine (LIST) mouth washes. A handheld spectrophotometer was used to measure the color attributes, and color differences (ΔE00) were then counted using specific equation. Data were analyzed using ANOVA and Tukey’s post-hoc tests. Results Significant differences in color change (ΔE00) values were observed between conventional and novel LS2 ceramics, as well as between different finishing methods and mouth-rinse solutions. Chlorhexidine induced higher color differences than Listerine, with average ΔE00 values of 0.959 and 0.885, respectively (p < 0.001). The polished specimens generally exhibited higher ΔE00 values than the glazed specimens, with average values of 1.071 and 0.792 for conventional LS2, and 0.836 and 0.786 for novel LS2 (p < 0.001). However, most color changes did not exceed the perceptibility and acceptability thresholds. Conclusion Using CHXD and LIST mouth washes affected the color change of polished or glazed conventional and novel lithium disilicate ceramics. In general, the stainability of polished specimens was higher than that of glazed ones. There was more discoloration on specimens immersed in CHXD than those immersed in LIST. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1178-1184